Home use of breast milk fortifier to promote postdischarge growth and breast feeding in preterm infants: a quality improvement project. Issue 10 (October 2019) - Marino, Luise V; Fudge, Carol; Pearson, Freya; Johnson, Mark John
Abstract : To improve the postdischarge growth of exclusively breastfed preterm infants, born weighing ≤1.8 kg, by using breast milk fortifier (BMF) supplements postdischarge until 48 weeks' gestational age. A quality improvement (QI) project involving plan–do–study–act (PDSA) cycles. A tertiary surgical neonatal unit. Preterm infants weighing ≤1.8 kg at birth. We completed four PDSA cycles to develop and improve an electronic patient information sheet to promote the use BMF beyond discharge. Safety, feasibility and attitudes of parents to home BMF were assessed using questionnaires. A retrospective audit (July 2015–September 2017) was completed investigating the effects of home BMF on growth up to 1 year of age. Change in SD scores for weight for age, length for age and head circumference of age at various time points compared with those at birth were calculated. Compared with baseline measurements (infants born October 2012–November 2013), the QI project resulted in improved growth (measured as the change in SD score from birth, cSDS) at discharge for weight (cSDS −0.7), head circumference (cSDS 0.4) and length (cSDS-0.8), and at 1 year for weight (cSDS 0.9) and length (cSDS 0.8). Home BMF appeared to be safe, and parents found its use acceptable. QI methods facilitated the successful integration of BMF into routine clinical care after discharge, improving the growth trajectory of exclusively breastfed preterm infants discharged home, as well as supporting breast feeding in this vulnerable population group.